On the Solvability of Superlinear and Nonhomogeneous Quasilinear Equations. (27th September 2009) - Jia, Gao; Zhao, Qing; Dai, Chun-yan
Abstract : Using Mountain Pass Lemma, we obtain the existence of nontrivial weak solutions for a class of superlinear and nonhomogeneous quasilinear equations. The key factor in this paper is to use the new idea of near p-homogeneity in conjunction with variational techniques to obtain a new multiplicity result for a vast set of nonlinear equations, such as the mean curvature equation and so on.